Eye clinic attendance at the olympic and paralympic games Rio 2016 and its correlation to the WHO indicators on eye health - Fernandes, A. G.; Bastawrous, A.; Ferraz, N. N.; Hennig, B.; Loduca Lima, V.; Galvao Viana, R.; Campos, M.; Marcello Furtado, J. (British Journal of Sports Medicine, 2021)
Objectives: To evaluate athletes` frequency of attendance at the eye clinic during the Olympic and Paralympic Games Rio 2016 and to correlate it to WHO core indicators on progress in ophthalmology care in a country.